EXPERIMENTAL CALIBRATION OF THE PHLOGOPITE FLUORIMETER AT 500-700°C AND 1-4 KBAR, AND ESTIMATED HF CONCENTRATIONS OF FLUIDS ASSOCIATED WITH MARBLE: SOME EXAMPLES - Aksyuk A.M.; Zhukovskaya T.N. (My University, 1994)
Fluorine distribution between (OH,F)-phlogopite and hydrothermal fluid has been experimentally investigated at 500–700°C and 1–4 kbar. Initial phlogopite compositions and HF concentrations in the HF-H2O fluid were varied from OH-phlogopite to F-phlogopite and from 0.001 to 0.1 mol/kg of H2O, respectively. Compositions of both phlogopite and solution were measured after the runs. The experimental data yield the following equation for the phlogopite fluorimeter: , where is a concentration in the fluid in mol/dm3 at temperature and pressure of interest; and are, respectively, the mole fractions of Mg and F in the octahedral and hydroxyl sites of phlogopite; is a water activity in fluid expressed as , where is a mole fraction and γ is a activity coefficient of water at T-P of fluid. The HF concentrations in natural fluids estimated by the fluorimeter equation range from 0.9·10−3 to 1.4·10−2 mol/dm3 for phlogopite formation in marbles of different localities: Adirondack Mountains (USA), Cairo del Diablo (Central Spain), Aldan Shield and Pribaikal'ye (Russia), and southwestern Pamir Mountains (Tajikistan).